Property law : rules, policies, and practices - Singer, Joseph William, 1954-; Berger, Bethany R.; Davidson, Nestor M.; Peñalver, Eduardo M., 1973- (Aspen casebook series., 2022)
"Casebook on Property law for law students; includes notes, questions, and problems"--